2015
DOI: 10.1080/10548408.2014.959153
|View full text |Cite
|
Sign up to set email alerts
|

Differences and Similarities in Perceptions of Hotel Experience: The Role of National Cultures

Abstract: This study focuses on demonstrating the differences and similarities between and among Western and Asian customers in terms of travelers' evaluation of satisfaction, perceived value, and attribute quality in a Hong Kong hotel setting. It has been noted that national culture has a substantial impact on travelers' expectations and perceptions. The results show that satisfaction, perceived value, and hotel attribute evaluations are significantly higher for Western than Asian travelers. We also found considerable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Finally, we did not consider any combined effects of service employee and guest nationalities. Therefore, employees’ and consumers’ emotions and behaviours should be further examined in different cultural contexts and other hospitality services (Zhang et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we did not consider any combined effects of service employee and guest nationalities. Therefore, employees’ and consumers’ emotions and behaviours should be further examined in different cultural contexts and other hospitality services (Zhang et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Many demographic and geographic factors of the reviewer have found to influence the reviews posted by them. For instance, the guest's national culture is shown to impact their hotel experience (Zhang et al, 2015(Zhang et al, , 2020, and thus on their reviews. Likewise, reviewers' perceived power distance is proven to have an inverse relationship on their ratings (Gao et al, 2018).…”
Section: The Influence Of Reviewer's Type-domestic Vs Foreignmentioning
confidence: 99%
“…Additionally, several prior studies have investigated whether the antecedents of user experiences and behavioral intentions are influenced by culture (Jahandideh et al, 2014;Sabioteortiz et al, 2016;Zhang et al, 2015). In the tourism context, websites and store brands have been attributed different levels of influence based on culture (Diallo and Siqueira, 2017;Moura et al, 2015).…”
Section: Cross-country Investigation Of O2o Channelsmentioning
confidence: 99%
“…Customers from different countries may have different evaluations of OTAs and hotels. Research has shown that country factors influence customers' evaluations of channels (Diallo and Siqueira, 2017;Jahandideh et al, 2014;Moura et al, 2015;Zhang et al, 2015). In this study, China and Indonesia are selected to investigate and compare consumer behavior because they are located in Asia, have high populations and high economic growth over the past decade and tourism accounts for 10-15% of the gross domestic product (GDP) in both countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation